Development of Automated Maynard Operation Sequence TEchnique (MOST) Work Study Technique: Case Study at Aerospace Manufacturing Company Using Lean Six Sigma - Abdullah, Rohana; Ahmad, Nurul Huda (2010)
Manufacturing industries nowadays is extremely interested with the term of Lean Six Sigma where the power of combining these two tools are belief able to help to increase the company performance and productivity due to the urgent need for survival in this challenging business. One of the applications of Lean Six Sigma is being used to study the method to perform work study in a manufacturing line. The Industrial Engineers (IEs) has been using stop watch and predetermined time standards (PTS) such as Maynard Operational Sequence Technique (MOST) to the perform work study. MOST, although is much more accurate than the stop watch method has its disadvantages since it is very tedious to perform the analysis. This project addresses the development of an automated MOST analysis system using Excel Macros and Visual Basics programming. This system provides the user with a template where information such as activity mapping, MOST index value will be entered by the user and the system will automatically determines the time measurement units (TMU) and converts the TMU value to the actual time measurement units. In addition to information on man to machine ratio and operator’s utilization, a histogram and Pareto diagram will also be generated automatically in order to graphically illustrate to the user the seven lean types of wastes for Kaizen improvements. A case study at an Aerospace Manufacturing Company was also conducted using Waterfall Model and Lean Six Sigma DMAIC methodology to test the effectiveness of the automated MOST and the system has proven to tremendously improve the efficiency of performing work study at this company.